U.S. Mutual Fund Retail Investors in International Equity Markets : Is the Tail Wagging the Dog? - Chan-Lau, Jorge (IMF Working Papers; Working Paper, 2005)
Do the dynamics of net flows to U.S. retail mutual funds affect equity returns in emerging markets? The question merits further examination since retail investors in mutual funds can exert a much greater degree of "control" over these funds via cash injections or redemptions at any time. A VAR analysis shows increased discrimination across emerging market regions after the Asian crisis as investors focused on individual regions rather than on emerging markets as a generic asset class. Crossover funds allocations also appear to affect emerging market returns. Furthermore, investment decisions by fund managers seem to be largely driven by retail investor allocations.